2012
DOI: 10.1088/0264-9381/29/24/245008
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of spherical charged anisotropic fluid spacetimes

Abstract: ABSTRACT. A class of spherical collapsing exact solutions with electromagnetic charge is derived. This class of solutions -in general anisotropic -contains however as a particular case the charged dust model already known in literature. Under some regularity assumptions that in the uncharged case give rise to naked singularities, it is shown that the process of shell focusing singularities avoidance -already known for the dust collapse [10] -also takes place here, determing shell crossing effects or a complete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Barreto and Rosales [18], extending their earlier approach in the diffusion regime, considered charged and self-similar spheres in the free-streaming approximations which is applicable in the early stages of collapse. Cipolletta and Giambo [19] found a class of charged anisotropic collapsing models and demonstrated that the shell focussing singularities may be avoided. The presence of charge in the gravitational collapse delays back hole formation and can even prevent collapse as shown by Pinheiro and Chan [20] by numerically integrating the fluid equations and stellar boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Barreto and Rosales [18], extending their earlier approach in the diffusion regime, considered charged and self-similar spheres in the free-streaming approximations which is applicable in the early stages of collapse. Cipolletta and Giambo [19] found a class of charged anisotropic collapsing models and demonstrated that the shell focussing singularities may be avoided. The presence of charge in the gravitational collapse delays back hole formation and can even prevent collapse as shown by Pinheiro and Chan [20] by numerically integrating the fluid equations and stellar boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Once the equation (5) has been prescribed, initial data for the system may be given assigning R at initial time. Without loss of generality we will take (6a) R(0, r) = r in such a way that an independent set of initial data, for example, is…”
Section: Isotropic Fluidsmentioning
confidence: 99%
“…Using Israel-Darmois junction condition, from (4b) it follows easily that a necessary and sufficient condition to match the solution with a Schwarzschild exterior is that the pressure p vanish on the matching surface. A milder condition which also fulfills physical requirements is to ask for a matching to a radiating metric such as the generalized Vaidya spacetime, as done for instance in [5].…”
Section: Isotropic Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakao et al [7] studied dynamical properties of collapsing cylindrically symmetric systems and claimed that there does not exist any physically reasonable cylindrical black hole. Cipolletta and Giambo [8] have explored analytical models for a class of charged spherical collapsing anisotropic fluids and found naked singularity under special condition. Thirukkanesh et al [9] have studied kinematical properties of anisotropic expanding shearing accelerating spherical compact objects.…”
Section: Introductionmentioning
confidence: 99%